Den Danske Folkekirkes Bekendelsesskrifter - Kristensen, Johanne Stubbe Teglbjærg; Enggaard, Nete Helene (Dansk Teologisk Tidsskrift, 2023)
In this article, we consider methodological challenges and promises for a contemporary Lutheran engagement with confessional writings. We approach the confessional writings of the Danish Evangelical Lutheran Church as both well-known and strange or even uncanny, and we consider five methodological issues in regard to their possible theology: (1) Their “difference and unity”, (2) their relation to the practice of the Danish church and their possible identity as “law”, (3) their relation to theology and academia, (4) their context(s) and genre(s) and, (5) their histories and function(s). Through this consideration, we argue for emphasizing the differences of the writings and for a conception of their unity as a seemingly paradoxical, but in fact reasonable, open and dynamic structure of differences. This implies an open, transformational or eschatological, “both-and” structure concerning their content and function; they are not perceivable as an abstract unity, not a law, not pure texts, not expressions of a single genre and not purely conservative documents. However, they also cannot be identified only as purely separated entities, powerless practices, unrelated and arbitrary, but through their differences, practices, contexts and histories, they expose new coherences and continuities. Through this, they contribute to confirmation and transformation of relations and events and they are, in this specific sense, writings for the future. They raise questions concerning contemporary conceptions of God, world and self and they indirectly contribute to answers beyond both the binaries and the totalities of the modern and postmodern situation.